Inverse plant model and frequency loop shaping-based PID controller design for processes with time-delay - Chakraborty S.; Naskar A.K.; Ghosh S. (My University, 2025)
To achieve satisfactory set-point tracking and load disturbance rejection, two approaches for PID controller design is presented in this paper. With a PD type controller, conventional IMC techniques fail to provide a satisfactory regulatory response for integrating processes and use of an integral action may lead to a large overshoot in servo response. To address this issue, a modified IMC structure with a second compensation for integrating processes is proposed to achieve desired servo as well as regulatory responses. Next, a frequency loop-shaping based design is proposed and the guidelines for choosing the desired loop-shape are also presented. To obtain the controller parameters in frequency loop-shaping framework, the optimisation problem is solved with primal-dual interior point method. To demonstrate the effectiveness of the proposed controllers, simulation comparisons with some recently developed methods are included. Moreover, the proposed method is experimentally validated on a temperature control process. Copyright © 2020 Inderscience Enterprises Ltd.